Implementation of the Family Hope Program in Sebuntal Village, Marangkayu District, Kutai Kartanegara Regency - Maharani Putri; Muhammad Noor; Melati Dama (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2021)
This research is intended to find out the implementation of the Family Hope Program in Sebuntal Village, Marangkayu District, Kutai Kartanegara Regency, whether PKH has so far been in accordance with implementation indicators in achieving goals, integrity, and adaptation and also to find out the factors that influence the Family Hope Program (PKH) in Sebuntal Village, Marangkayu District, Kutai Kartanegara Regency. This study used descriptive qualitative method. The location is in Sebuntal Village, Marangkayu District, Kutai Kartanegara Regency. Data collection was carried out by library research, observation, in-depth interviews, and documentation techniques. Data analysis was carried out by collecting data, condensing data, presenting data, and drawing conclusions or verifying data. The results of this study indicate that the success of the implementation of the Family Hope Program in Sebuntal Village, Marangkayu District, in general, can be said to be running smoothly even though there are some beneficiaries who have not been on target.